The psychosocial well-being of sub-Saharan African migrant parents in Ontario: a scoping review - Tsinat Semagn; Ingrid Waldron; Allison Williams; Sarah Qureshi; Olive Wahoush (Discover Public Health)
Abstract Objective The primary objective of this scoping review is to evaluate the breadth of existing literature on the psychosocial well-being of sub-Saharan African (SSA) migrant parents living in Ontario, Canada. Introduction Ontario, the most populous province in Canada, has seen a significant influx of migrants from SSA in the past several years, with Nigeria and South Africa being the top countries of origin of Black African newcomers. Conditions resulting from overcrowding and provincial attempts to accommodate this influx have led to medium-sized cities, like Hamilton and Ottawa, and small communities becoming increasingly popular destinations for immigrants. Methods This review was conducted according to the JBI guide on evidence synthesis and the results were organized and reported in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR). An extensive search strategy was developed for application across six databases: PubMed, Scopus, ProQuest, Web of Science, OVID, and CINAHL. The findings demonstrate high level of heterogeneity between studies, which were appraised independently by two researchers using the QuADS tool. Results 15 articles were included in the scoping review. The review revealed five major themes related to the psychosocial well-being of Black African migrant parents: (1) psychosocial well-being as a culturally embedded concept, (2) the politicization of health and its impact on psychosocial well-being, (3) generational dynamics and parenting challenges, (4) the interplay of trauma and resilience in the resettlement journey, and (5) agency and resourcefulness of Black African migrant parents.